Contrasting rule and machine learning based digital self triage systems in the USA - Bilal A. Naved; Yuan Luo (npj Digital Medicine)
Abstract Patient smart access and self-triage systems have been in development for decades. As of now, no LLM for processing self-reported patient data has been published by health systems. Many expert systems and computational models have been released to millions. This review is the first to summarize progress in the field including an analysis of the exact self-triage solutions available on the websites of 647 health systems in the USA.